The Kynurenine Pathway and Polycystic Ovary Syndrome: Inflammation as a Common Denominator. (May 2022) - Jovanovic, Filip; Sudhakar, Aboorva; Knezevic, Nebojsa Nick
Polycystic ovary syndrome (PCOS) is a complex metabolic disorder commonly seen in females of reproductive age. The pathophysiology of PCOS is multifactorial and includes dysfunction in ovarian steroidogenesis and folliculogenesis, impaired gonadotropin levels, insulin resistance, gut microbiota imbalance, genetic predisposition, and lifestyle preferences. Low-grade inflammatory conditions such as obesity and impaired glucose tolerance are common metabolic disturbances in women with PCOS. A growing body of literature suggests strong evidence rendering PCOS in close proximity with chronic inflammation as documented by high levels of serum white blood cells, C-reactive protein, and various proinflammatory cytokines seen in this condition. Inflammation seems to be the most common metabolic denominator between the kynurenine pathway and PCOS. The association of tryptophan and kynurenine pathway has already been well documented in mood disorders, neurodegenerative diseases, chronic pain conditions, and different inflammatory states. In this manuscript, we describe the influence of sex steroid hormones on different enzymes of the KP; inflammatory nature of PCOS and CRP as a marker of IDO/TDO activity; and the effects of altered gut flora in women with PCOS. This review provides a novel view of the available evidence of tryptophan and downstream metabolites in PCOS in the context of underlying inflammation.